An exploratory study of the relationship between psychological support and resilience in adolescent orphans - Mudau, Tondani (My University, 2018)
This study aimed to explore the relationship between psychosocial support and resilience in adolescent orphans residing in a rural area of the Vhembe District, Limpopo province, South Africa. The study explored this relationship by adopting a qualitative research design and employed a hermeneutic method of phenomenology as an epistemology for understanding the participants’ different subjective experiences and realities. The study utilised semi-structured interviews with open-ended questions written in both English and Tshivenda. The interview questions, participant information letter, assent and consent forms were all translated from English to Tshivenda to ensure comprehension and voluntary participation. To recruit participants purposive and convenience sampling procedures were utilised. The participants were selected on a single and double orphan criteria; the process entailed approaching the social worker to select participants who met the criteria. Thereafter, the sample consisted of 11 participants, male (n=4) and female (n=7) between the ages of 13 and 18. To understand the relationship between psychosocial support and resilience, this research draws upon the Social-Ecological Resilience Framework (Ungar, 2011). Social-Ecological Resilience Framework paves a way of understanding an individual in their own context, by focusing on their social relations, societal discourses and ideological positions. From Thematic Analysis the themes of support such as caregiver support, educational support, environmental safety, health support, spiritual support and peer relationships were themes associated with resilience. Thematic analysis has shown that psychosocial support plays an important role in the promotion of adolescent orphans’ resilience.
This research report is submitted in partial fulfilment of the requirement for a Master’s Degree in Research Psychology by Coursework and Research Report in the Department of Psychology Faculty of Humanities, School of Human and Community Development at the University of the Witwatersrand. Johannesburg, 2018
Keywords: Resilience (Personality trait) in adolescence--South Africa; Youth--Services for; Youth--Mental health--South Africa